Device-based therapies for arterial hypertension - Lauder, Lucas; Azizi, Michel; Kirtane, Ajay J; Böhm, Michael; Mahfoud, Felix (Nature reviews cardiology, 2020)
Arterial hypertension is the most prevalent modifiable risk factor associated with cardiovascular morbidity and mortality. Although antihypertensive drugs are widely available, in many patients blood pressure control to guideline-recommended target values is not achieved. Several device-based approaches have been introduced to lower blood pressure; most of these strategies aim to modulate autonomic nervous system activity. Clinical trials have moved from including patients with resistant hypertension receiving intensive pharmacological treatment to including patients with mild-to-moderate hypertension in the presence or absence of antihypertensive medications. Renal sympathetic denervation is the most extensively investigated device-based therapy for hypertension, and randomized, sham-controlled trials have provided proof-of-principle data for its blood pressure-lowering efficacy. Unilateral electrical baroreflex activation, endovascular baroreflex amplification and pacemaker-mediated cardiac neuromodulation therapy have yielded promising results in observational trials, which need to be confirmed in larger, adequately powered, sham-controlled trials. Until further evidence becomes available, device-based therapy for hypertension should not be considered for routine treatment. However, when considering a device-based treatment for hypertension, the underlying pathophysiology in each patient has to be taken into consideration, and the procedural risks weighed against the cardiovascular risk attributable to the elevated blood pressure. This Review summarizes the pathophysiological rationale and the latest clinical evidence for device-based therapies for hypertension.